2018
DOI: 10.1111/ggi.13275
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rivastigmine on plasma butyrylcholine esterase activity and plasma ghrelin levels in patients with dementia in Alzheimer’s disease

Abstract: The present study suggests that rivastigmine might improve appetite in mild-to-moderate Alzheimer's disease patients by suppressing degradation of plasma active ghrelin through the inhibition of plasma butyrylcholine esterase. Geriatr Gerontol Int 2018; 18: 886-891.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Also, rivastigmine, which has dual inhibitory effects on acetylcholinesterase and butyrylcholinesterase, could improve appetite. 28 Although psychotropic medications, such as major tranquilizers and antidepressants, temporarily increase appetite, the present results showed that their use in persons with AD was positively correlated with poor appetite. This might be because the incidence of adverse events due to psychotropic drugs increases with advancing dementia, and excessive sedation and induction of somnolence due to the use of psychotropic drugs occurs in persons with AD.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Also, rivastigmine, which has dual inhibitory effects on acetylcholinesterase and butyrylcholinesterase, could improve appetite. 28 Although psychotropic medications, such as major tranquilizers and antidepressants, temporarily increase appetite, the present results showed that their use in persons with AD was positively correlated with poor appetite. This might be because the incidence of adverse events due to psychotropic drugs increases with advancing dementia, and excessive sedation and induction of somnolence due to the use of psychotropic drugs occurs in persons with AD.…”
Section: Discussionmentioning
confidence: 42%
“…This might be due to an improvement of apathy. Also, rivastigmine, which has dual inhibitory effects on acetylcholinesterase and butyrylcholinesterase, could improve appetite …”
Section: Discussionmentioning
confidence: 99%
“…; Table ). One potential underlying mechanism for this might be that rivastigmine suppresses the degradation of plasma ghrelin by inhibiting plasma BuChE . Ghrelin is a gastrointestinal tract hormone known to increase appetite .…”
Section: Discussionmentioning
confidence: 99%
“…One potential underlying mechanism for this might be that rivastigmine suppresses the degradation of plasma ghrelin by inhibiting plasma BuChE. 23 Ghrelin is a gastrointestinal tract hormone 5 known to increase appetite. 6,7 Further potential mechanisms for this improvement of appetite in patients with AD might be both the inflammatory effects of ChEI in cholinergic pathways, and their ability to improve smell and taste perception by increasing the acetylcholine concentration in olfactory mucosa and taste buds, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Galantamine-induced adiponectin augmentation and HOMA-IR amelioration have been reported so far in one study in young adults with metabolic syndrome within 4 weeks [ 165 ]. On the contrary, rivastigmine, capable also of inhibiting the ghrelin degrading enzyme butyrylcholine esterase, has a direct effect on appetite and the prevention of weight loss, without affecting leptin levels [ 166 , 167 ].…”
Section: Energy Balance Micronutrient Deficiencies and Adipokinesmentioning
confidence: 99%